Linguistic diversity in the classroom, student achievement, and social integration - Julia Bredtmann; Sebastian Otten; Christina Vonnahme (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
In this article, we analyze whether non-native speakers in the classroom affect the educational achievement and social integration of migrant and native students. In contrast to previous studies, which mainly examine the effect of the share of immigrant pupils, we focus on language heterogeneity by using a novel measure of the degree of linguistic diversity in the classroom. Our analysis is based on a comprehensive survey of 4th-grade students in German primary schools, which contains detailed information on students' language and math scores, their social integration, as well as on sociodemographic and school characteristics. We find a negative association between the share of non-native speakers in the classroom and students' test scores and their social integration in the class. Conditional on the immigrant concentration in the class, the degree of linguistic diversity has no adverse effect on students' language and math skills, but worsens the social integration of immigrant students. We demonstrate the robustness of these findings in a variety of robustness checks. – – Dieser Artikel untersucht den Einfluss von Nicht-Muttersprachlern in der Schulklasse auf den Bildungserfolg und die soziale Integration von Kindern mit und ohne Migrationshintergrund. Im Gegensatz zu bisherigen Studien, die vor allem den Effekt des Anteils an Migranten in der Klasse oder Schule untersuchen, konzentrieren wir uns auf die sprachliche Zusammensetzung der Schülerschaft und nutzen hierfür ein neuartiges Maß für die sprachliche Diversität in der Schulklasse. Die empirische Analyse basiert auf einer umfangreichen Befragung von Viertklässlern in deutschen Grundschulen, die detaillierte Informationen zu den Testergebnissen in Deutsch und Mathe der Schüler, deren sozialer Integration, sowie soziodemografischen und Schulcharakteristika enthält. Unsere Ergebnisse zeigen einen negativen Zusammenhang zwischen dem Anteil an Nicht-Muttersprachlern in der Klasse und den Testergebnissen sowie der sozialen Integration der Schüler. Gegeben des Anteils an Nicht-Muttersprachlern in der Klasse hat die sprachlicher Diversität der Nicht-Muttersprachler keinen Einfluss auf die Testergebnisse der Schüler. Kinder mit Migrationshintergrund sind in Klassen mit einer hohen Diversität jedoch schlechter sozial integriert. Wir zeigen die Robustheit unserer Ergebnisse in diversen Sensitivitätsanalysen.
Keywords: I21; I24; J15; 330; linguistic diversity; educational performance; social integration; migrant peer effects